The Logic of U.S. Deployment in Norway: The Trump Administration and NATO’s Northern Front - Dylan Motin (Journal Of Global Strategic Studies, 2024)
Observers generally assume that domestic concerns or Donald Trump’s personality oriented his administration’s foreign policy. In this piece, I discuss the United States’s decision in 2017 to base military forces in Norway. I argue that the Trump administration’s decision is mainly explainable by balance-of-power motives and has little to do with domestic concerns. After showing the importance of Norway to the United States and describing the military balance of power in Northern Europe, this study tests competing IR theories. It is clear that realism and balance-of-power theory are far more amenable for describing U.S. policy toward Norway.